Characteristics of landfill leachates and bio-solids of municipal solid waste (MSW) in Riyadh City, Saudi Arabia - M.I. Al-Wabel; W.S. Al Yehya; A.S. AL-Farraj; S.E. El-Maghraby (Journal of the Saudi Society of Agricultural Sciences)
The liquid and bio-solids (landfill sediments) product from landfills has many toxic substances, which may adversely affect on the environmental health. Thus in order to have a better management of characteristics of Riyadh landfill leachates, 80 representative landfill leachate samples were collected and analyzed from February to May 2008. The analysis of landfill leachates includes pH, ECw, concentrations of soluble ions, chemical oxygen demand (COD), total suspended solids (TSS), and heavy metals contents. The obtained results showed that the landfill leachates are characterized by high concentrations of COD (13,900–22,350) mg L−1, TSS of (2280–8912) mg L−1, ECw values of (42.5–58.3) dS m−1 but the pH values ranged 5.49–6.32. Moreover, the leachates had higher concentrations of soluble Na+, K+, Ca2+, Mg2+, Cl−, HCO3- and SO42-. In addition, the leachates contained Fe, Mn, As, Ni, Cr, Zn and Cu in concentrations equivalent to: 104, 11.0, 1.4, 0.6, 0.25, 0.2 and 0.14 mg L−1, respectively. While in the bio-solids (landfill sediments) the average content of Cd, Cr, Cu, Fe, Mn, Mo, Ni and V reached to 10, 242, 234, 48,608, 190, 18, 166 and 24 mg kg−1. The relatively higher variations between the upper and lower limits (maximum and minimum values) of the studying parameters lead to conclude that it is essential to conduct a long-term monitoring program to obtain representative information and this fluctuation should be considered when operating the leachate treatment plant.